PSYCHOLOGICAL COMPLAINTS AMONG AMPUTEES IN SELECTED HOSPITALS PESHAWAR (Journal of Medical & Health Sciences Review, 2025)
Background: Amputation is a life-altering surgical intervention performed to prevent severe complications from conditions such as trauma, vascular disorders, infections, or malignancy. It not only results in permanent physical disability but also imposes profound psychological challenges, including stress, anxiety, and depression. Globally, approximately 1.7 million people are living with limb loss in the United States alone. In Pakistan, data remain scarce despite the rising prevalence of amputations due to diabetes, trauma, and war-related injuries. Understanding the psychological complaints of amputees is crucial for designing effective rehabilitation and support strategiesObjectives: The main aim of this study was to assess psychological complaints of amputees in the selected hospitals of Peshawar.Methods: A descriptive cross-sectional study was conducted on 128 amputee patients recruited through purposive sampling from Hayatabad Medical Complex, Lady Reading Hospital, Khyber Teaching Hospital, and the Pakistan Institute of Prosthetic and Orthotic Sciences. Data were collected using the Depression, Anxiety, and Stress Scale (DASS-42). SPSS version 22 was used for statistical analysis.Results: A Total of 128 participants, 90% were male, and the mean age was 40.6 ± 15.2 years. Most participants (89.8%) had unilateral lower-limb amputations, with bomb blasts (25%), road traffic accidents (22.7%), and diabetes mellitus (21%) identified as the leading causes. Findings revealed that 50.7% of amputees experienced stress, 44.5% reported anxiety, and 40.6% suffered from depression. Significant associations were observed between gender and both anxiety (p=0.00) and depression (p=0.01), whereas other demographic variables showed no significant correlation.Conclusion: It is concluded that Amputees in Peshawar experience a high prevalence of psychological complaints, particularly stress, anxiety, and depression. The findings underscore the urgent need for integrated psychosocial support and multidisciplinary rehabilitation programs. Nurses and healthcare professionals play a pivotal role in identifying and addressing these psychological needs to improve the overall quality of life for amputees.